Issues and challenges in defining a heat wave: A Mediterranean case study - Bárcena-Martín, Elena María; Molina-Luque, Julián; Ruiz-Sinoga, José Damián (Royal Meteorological Society, 2019)
We evaluated three definitions of heat wave (HW) and demonstrate that selection of the reference period and air temperature threshold used in the definition can affect the reported frequency of HWs. First, we propose an alternative definition of HW that is based on a moving reference period and specific air temperatures threshold for each calendar date. Then, we present a case study using data from five observatories in Malaga Province (Spain) from 1971 to 2016. We assessed the effect of a moving reference period (rather than a fixed reference period) and the definition of daily air temperatures threshold on the identification of anomalies in the definition of a HW. The results indicate that HWs can occur throughout the year. Finally, we propose incorporation of minimum daily air temperatures in two alternative definitions of HW. Our results indicate a high frequency of HWs in the summer months, in which HWs are mainly due to anomalous high Tmin and more frequent HWs in which maximum and minimum daily air temperature are exceeded from 2014 onwards. These new methods of defining a HW provide more accurate assessments of thermal discomfort.
Keywords: Cambios climáticos; Calor - Mediterraneo; Daily threshold; Heat waves; Maximum air temperature; Minimum air temperature; Moving reference period